THE ROLE OF PHONETIC RHYTHMIC ACTIVITIES IN NATIONAL SURDOPEDAGOGY - Ozodaxon Sirodjovna Ishmatova (European Science Publishing, 2025)
This article explores the effectiveness of phonetic rhythmic activities in the development of speech in deaf and hard-of-hearing children. The study analyzes how phonetic rhythmic exercises, through sensory integration, music, and physical movement, contribute to speech development. Furthermore, it demonstrates how this method can be effectively applied in shaping pronunciation, developing speech skills, and enhancing socialization in deaf and hardof- hearing children. The research confirms that phonetic rhythmic activities are one of the most effective corrective methods for these children and emphasizes the need for broader implementation in educational processes.
Keywords: Phonetic rhythmics, deaf children, hard-of-hearing children, speech development, sensory Integration, music, physical movement, pronunciation, corrective methods, socialization, pedagogical processes.